2004
DOI: 10.1111/j.1742-1241.2004.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function studies in Kuwaiti children with sickle cell disease and elevated Hb F

Abstract: Conflicting ventilatory defects have been reported in children with sickle cell disease (SCD). In Kuwait, the disease is relatively mild with a low incidence of acute chest syndrome and other complications, presumably due to the Arab-Indian haplotype chromosomal background and elevated Hb F levels. There have been no previous studies of pulmonary function in patients with this haplotype. Pulmonary function test (PFT) was carried out on 28 steady state children with SCD (21 homozygous sickle cell (SS), seven S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…In a previous study from our center, SCD patients had the lowest PFT parameters when compared to normal controls and patients with HbH disease [16]. In a study from India, which also looked at children with SCD and elevated fetal Hb levels, Purohit et al [29] reported significantly lower values of FEV 1 and FVC in the patients compared to healthy controls, similar to the results from the present study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a previous study from our center, SCD patients had the lowest PFT parameters when compared to normal controls and patients with HbH disease [16]. In a study from India, which also looked at children with SCD and elevated fetal Hb levels, Purohit et al [29] reported significantly lower values of FEV 1 and FVC in the patients compared to healthy controls, similar to the results from the present study.…”
Section: Discussionsupporting
confidence: 80%
“…There has been only one previous study of pulmonary function in these patients and it showed early signs of abnormality that were unrelated to their level of anemia [16]. However, other genetic and environmental factors associated with pulmonary function were not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lung disease associated with SCD, on the other hand, manifests as interstitial abnormalities on CXR or impaired pulmonary function testing. Both restrictive and obstructive pattern have been encountered 94 . In its most severe form, SCD can manifest itself in the form of pulmonary hypertension (Fig.…”
Section: Pulmonary Pathology In the Middle Eastmentioning
confidence: 99%
“…However, there is still no consensus on whether SCD is causing a specific lung function abnormality . Several mechanisms have been implicated in the pathogenesis of the pulmonary complications including airway reactivity and asthma but the exact timing and mechanism(s) involved remain unclear . In this issue of the Journal, Lunt and colleagues present a study of longitudinal follow‐up of lung function in 2 cohorts of children with SCD .…”
Section: Comparison Of Longitudinal Changes In Lung Function Indices mentioning
confidence: 99%